Antithrombin During Extracorporeal Membrane Oxygenation in Adults: National Survey and Retrospective Analysis. Issue 3 (March 2019) - Iapichino, Giacomo E.; Protti, Alessandro; Andreis, Davide T.; Panigada, Mauro; Artoni, Andrea; Novembrino, Cristina; Pesenti, Antonio; Gattinoni, Luciano
Abstract : The impact of antithrombin replacement during extracorporeal membrane oxygenation (ECMO) in adults remains unclear. This work comprises a survey, showing that antithrombin is routinely supplemented in many Italian ECMO-Centers, and a retrospective analysis on 66 adults treated with veno-venous ECMO and unfractionated heparin at our Institution. Twenty-four to 72 h after the beginning of ECMO, antithrombin activity was ⩽70% in 47/66 subjects and activated partial thromboplastin time (aPTT) ratio was <1.5 in 20/66 subjects. Activated partial thromboplastin time ratio <1.5 was associated not with lower antithrombin activity (61 ± 17 vs . 63 ± 22%; p = 0.983) but with higher circulating level of C-reactive protein (23 ± 8 vs . 11 ± 9 mg/dl; p < 0.001). In 34 subjects who received antithrombin concentrate, antithrombin activity increased (from 54 ± 9 to 84 ± 13%; p < 0.001); the proportion of subjects with aPTT ratio ≥1.5 increased (from 21/34 [62%] to 31/34 [91%]; p = 0.004); heparin dosage remained constant (from 19 ± 7 to 19 ± 6 IU/kg/h; p = 0.543); and C-reactive protein decreased (from 17 ± 10 to 13 ± 9 mg/dl; p = 0.013). Among those with aPTT ratio <1.5, aPTT ratio remained <1.5 in 3 out of 13 subjects. Antithrombin is frequently supplemented during veno-venous ECMO although low antithrombin activity does not constantly impede, and antithrombin replacement does not constantly ensure, reaching the target aPTT ratio. Inflammation possibly affects the individual response to heparin. Abstract : Supplemental Digital Content is available in the text.